2009
DOI: 10.1152/ajpendo.00217.2009
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Fas in the pancreatic β-cells leads to enhanced insulin secretion

Abstract: Fas/Fas ligand belongs to the tumor necrosis factor superfamily of receptors/ligands and is best known for its role in apoptosis. However, recent evidence supports its role in other cellular responses, including proliferation and survival. Although Fas has been implicated as an essential mediator of β-cell death in the pathogenesis of type 1 diabetes, the essential role of Fas specifically in pancreatic β-cells has been found to be controversial. Moreover, the role of Fas on β-cell homeostasis and function is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Exendin-4 (Sigma, St Louis, MO, USA) in PBS was administrated i.p. at 09:00 hours and 17:00 hours for 3 days at a dose of 24 nmol/kg [20]. Glucose tolerance tests (GTT), insulin tolerance tests (ITT) and glucose-stimulated insulin secretion (GSIS) were performed as previously described [21].…”
Section: Methodsmentioning
confidence: 99%
“…Exendin-4 (Sigma, St Louis, MO, USA) in PBS was administrated i.p. at 09:00 hours and 17:00 hours for 3 days at a dose of 24 nmol/kg [20]. Glucose tolerance tests (GTT), insulin tolerance tests (ITT) and glucose-stimulated insulin secretion (GSIS) were performed as previously described [21].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has reported that Fas is essential for ␤-cell insulin-secretory function but not in the regulation of ␤-cell mass (42). Another study has shown that islet-specific Fas deletion is protective against FasL-and ceramide-induced apoptosis ex vivo and enhances ␤-cell insulin secretion in vivo (8). These discrepancies may be linked to differences in genetic backgrounds of the mouse strains used in these two studies.…”
Section: E562 Role Of Fas In the ␤-Cells Of C-kitmentioning
confidence: 96%
“…Previous ex vivo studies with human pancreatic ␤-cells have shown that glucotoxicity-induced ␤-cell apoptosis occurs via upregulation of the Fas-mediated apoptotic pathway, which could be rescued by downregulation of Fas (25,36). Furthermore, deletion of Fas in rodent pancreatic ␤-cells has shown protection against FasL-induced apoptosis and increased in vivo insulin secretion (8). While much evidence has pointed to Fas as an important mediator of ␤-cell apoptosis, downstream caspase-8 and -3 are also well known for their roles as the principal executioners of ␤-cells.…”
Section: E561 Role Of Fas In the ␤-Cells Of C-kitmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Both forms of diabetes are causally linked to (absolute or relative) β-cell deficiency, 12 and in many instances attributed to increased β-cell apoptosis. [13][14][15] However, targeting β-cell apoptosis has either been incompletely successful in preventing diabetes, 16 or has unmasked latent oncogenic potential. 17 These results point to a parallel programmed death pathway in pancreatic β-cells.…”
Section: Pancreatic β-Cell Deficiency In Diabetes; Apoptosis or Progrmentioning
confidence: 99%